Factors influencing the uptake of short-term contraceptives among women in Afghanistan - Noormal, Ahmad Siyar; Winkler, Volker; Eshraqi, Ali Maisam; Deckert, Andreas; Sadaat, Iftekhar; Dambach, Peter (Scientific reports, 2022)
The aim of this study is to assess factors that influence the uptake of short-term contraceptives among married women aged between 15 and 49 years in Afghanistan. The cross-sectional Afghanistan 2015 Demographic and Health Survey provided the dataset for this analysis. We included 22,974 women and applied multivariable logistic regression to investigate the influencing factors for the uptake of short-term contraceptives. 92% of Afghan women knew at least one type of short-term contraception but only 17% were using short term contraceptives. Short term contraceptive use was most prevalent among women in the age group between 30 and 40 who were educated, employed, and rich. Most of the users were living in the western parts of Afghanistan and women from the Balooch and Pashtun ethnic groups were most likely to use short-term contraceptives. Media exposure and women empowerment were also positively associated with the use of short-term contraceptives. We did not find an association with living in urban or rural settings. Contraception promotion in Afghanistan requires multisectoral efforts, tailored to the needs of women from low and middle socioeconomic strata. Health promotion activities, empowering women, strengthening education, and training of service providers on effective counseling are options that should be considered to improve the current situation.